[18F]FDG PET/CT imaging of colorectal cancer: a pictorial review. Issue 1013 (17th March 2010) - Chowdhury, Fahmid U; Shah, Nehal; Scarsbrook, Andrew F; Bradley, Kevin M
Abstract : Integrated positron emission tomography/CT (PET/CT) with 2-[ 18 F]fluoro-2-deoxy-d -glucose (FDG) is a hybrid imaging modality which has recently become established in the staging, restaging and therapy response assessment of oncology patients. FDG PET/CT has several recognised applications in colorectal cancer (CRC) imaging including preoperative evaluation of apparently limited metastatic disease, detection of disease recurrence, clarification of equivocal lesions at initial staging, investigation of unexplained rising tumour markers, and incidental detection of occult primary colonic tumours. With a constantly advancing body of evidence and increasing availability, applications of PET/CT in CRC are likely to emerge in therapy response assessment, radiotherapy planning, use of novel tracers and 'one-stop' imaging techniques such as iodinated contrast-enhanced PET/CT. With the use of illustrative clinical examples, this article reviews the utility of FDG PET/CT in the management of CRC, discussing its role and limitations in the multimodality imaging of these patients.